2012
DOI: 10.1016/j.jeconom.2011.09.030
|View full text |Cite
|
Sign up to set email alerts
|

Estimating semiparametric panel data models by marginal integration

Abstract: We propose a new methodology for estimating semiparametric panel data models, with a primary focus on the nonparametric component. We eliminate individual effects using first differencing transformation and estimate the unknown function by marginal integration. We extend our methodology to treat panel data models with both individual and time effects. And we characterize the asymptotic behavior of our estimators. Monte Carlo simulations show that our estimator behaves well in finite samples in both random effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
50
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 39 publications
0
50
0
Order By: Relevance
“…4 Asymptotic properties of this estimator are derived in Qian and Wang (2012). In practice, we use a plug-in bandwidth that minimizes estimated asymptotic mean integrated squared error (AMISE).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Asymptotic properties of this estimator are derived in Qian and Wang (2012). In practice, we use a plug-in bandwidth that minimizes estimated asymptotic mean integrated squared error (AMISE).…”
Section: Methodsmentioning
confidence: 99%
“…samples I i,t−1 from the distribution f (·) and then we construct the estimator, m(I i,t ) = 1 n n i=1 g(I i,t , I i,t−1 ) using numerical integration. This approach is non-iterative (unlike that in Henderson et al, 2008), easy to implement in practice and has been shown to perform well in finite samples (Qian and Wang, 2012). …”
Section: Methodsmentioning
confidence: 99%
“…Not only can the model in (1.1) be conveniently applied to reduce the "curse-of-dimensionality" problem, but it also nests purely nonparametric fixed-effects panel data models as well as partially linear fixed-effects panel data models studied by Henderson, Carroll & Li (2008), Qian & Wang (2012) and Li & Liang (2015), who all however focus on a rather restrictive case of d g = 0.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the literature on non-and semiparametric panel models is based on the assumption that the regression function is the same across individuals; see Henderson et al (2008), Mammen et al (2009) and Qian and Wang (2012) among many others. This assumption, however, is very unrealistic in many applications.…”
Section: Introductionmentioning
confidence: 99%